Specialization, gravity, and European trade in final goods - Richard Frensch; Jan Hanousek; Evžen Kočenda (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
We suggest that bilateral gravity equations augmented by ad hoc measures of absolute supply-side country differences are misspecified. Building on Haveman and Hummels (2004), we develop and test an alternative specification rooted in incomplete specialization that views bilateral gravity equations as statistical relationships constrained on countries' multilateral specialization patterns. According to our results, specialization incentives seem not to play much of a role in the average European bilateral final goods trade relationship. However, this aggregate view conceals that trade in final goods between Western and Eastern Europe is driven by countries' multilateral specialization incentives, as expressed by supply-side country differences relative to the rest of the world, fully compatible with incomplete specialization models. This indicates that many of the final goods traded between Western and Eastern Europe are still different, rather than differentiated, products.
urn:nbn:de:101:1-20121001721
Keywords: F14; F16; L24; 330; international trade; gravity models; panel data; European Union; Internationale Wirtschaft; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Internationale Arbeitsteilung; Panel; EU-Staaten; Westeuropa; Osteuropa